Exchange rate policy in Republic of Serbia in conditions of the global economic crisis and Covid-19 pandemic: Similarities and differences - Dimić Maja; Stanković Ljiljana; Todorović Milica (Trendovi u Poslovanju)
The foreign exchange market represents the direct connection between a national economy and the global environment. The smooth functioning of the foreign exchange market contributes to national financial markets increasingly establishing relationships. The increase in the number of countries that have established currency convertibility and the rapid development of telecommunication technologies have primarily encouraged the foreign exchange market to develop at an astonishing speed. The efficiency of a national economy is best seen in the foreign exchange market through the price of the domestic currency, i.e. the exchange rate. The topic of the paper is the foreign exchange market and the dinar exchange rate, with a primary focus on the functioning of exchange rates and the analysis of foreign exchange markets during global financial crises in the period 2008-2010 and during the 2019-2021 crisis caused by the Covid-19 pandemic. In addition to the analysis of these two major crises, the effects of which were reflected on the Serbian economy as a whole, the similarities and differences of their impact on the foreign exchange market in Serbia are also listed here.